PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING DALAM PEMBELAJARAN TERHADAP PEMBENTUKAN KARAKTER SISWA DI ERA PEMBELAJARAN ONLINE - Tambunan, Janwar (Jurnal Suluh Pendidikan, 2022)
The purpose of this study was to see the effect of the Quantum Teaching learning model used by Christian Religious Education teachers in the formation of student character. The sample in this study was 50 people. This study used descriptive methods, while the data analysis carried out in the hypothesis research was Pearson's product moment correlation with data collection tools, namely a questionnaire for Variable X (Influence of Quantum Teaching Learning Model) and Variable Y (Student Character Building) The statistical test used in this research is using the Pearson Product Moment Correlation statistical test. From the test results obtained correlation test (r) 0.96 with a determination test of 92% and to determine whether or not the correlation coefficient is significant at the real level (α) = 0.05, the "t" test is held. From the test results obtained tcount > ttable (3.19 > 1.67), then the hypothesis is accepted. Thus, it can be stated that there is an influence of the Quantum Teaching Learning model in PAK learning on the character formation of students in the era of online learning. Keywords : Learning Model; Quantum Teaching; Student Character